Dry-Heat Conjugation Improves the Stability of Whey Protein-Stabilized Emulsions under Electrolyte and Heat Treatments - A'yun, Qurrotul; Hidayat, Chusnul; Van der Meeren, Paul (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2026)
Dry-heat conjugation of whey protein with its innate lactose has successfully improved the heat stability of whey protein concentrate (WPC) when applied as an emulsifier. However, the emulsion stability was only measured towards heating. Meanwhile, other stress conditions such as the presence of electrolyte may also be involved during processing. Understanding the latter could largely enhance the industrial application of conjugates. To achieve that goal, the current study examined the ability of whey protein-lactose conjugates to stabilize oil-inwater (o/w) emulsions towards the presence of electrolytes (CaCl2 ) by adding 5 mM of CaCl 2 in the aqueous phase during emulsion preparation, towards storage at refrigerator temperature (4 o C). Furthermore, the stability of emulsions in the presence of electrolyte were evaluated towards thermal stress conditions (i.e. heating at 60 and 80 o C for 30 minutes) followed by particle size and emulsion evaluation. Furthermore, the properties of the conjugates which may influence these functionalities were also investigated. The results indicated the enhanced ability of whey protein-lactose conjugates as an emulsifier to stabilize the emulsions upon applying destabilizing forces. Especially, conjugates obtained upon 8 hours dry heating (18% conjugation degree) exhibited the best stabilization capacity. They retained the submicron emulsion upon a combination of electrolyte addition and heat treatment. The conjugate-stabilized emulsions also showed delayed creaming and a prolonged storage stability. This improved functional properties may had been resulted from the enhanced water binding ability of the protein conjugates as revealed by the time domain nuclear magnetic resonance (TD-NMR) assay. These results denoted the potential application of the obtained whey protein-lactose conjugates as an efficient emulsifier with improved emulsion stabilizing capacities.